Vālmīki's Rāmāyaṇa - Vālmīki (Rowman & Littlefield, 2018)
Translator's note to the updated edition -- Translator's note -- Introduction -- Childhood -- Ayodhy -- Wilderness -- Kīkindha -- Beauty -- War -- Epilogue -- Glossary -- Notes